2010
DOI: 10.1002/srin.201000016
|View full text |Cite
|
Sign up to set email alerts
|

Transient Flow and Inclusion Removal in Gas Stirred Ladle during Teeming Process

Abstract: A water model of a typical 150t ladle was designed and constructed to determine the flow characteristics. A kind of organic emulsion was selected to model nonmetallic inclusion particles with the purpose of studying the inclusion removal effect under gas blowing in a teeming ladle. The presented modeling method for inclusion particles in the teeming process is different from those under steady condition. The numerical simulation was performed by using commercial software with the Eulerian‐Eulerian multiphase m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Consequently, there are vortexes on both sides of the gas jet flow, and these vortexes are near the free surface. Some researchers [ 37 , 38 ] used the Euler–Euler approach to describe the fluid flow in the gas-stirred ladle and indicated that the width of the plume remained almost unchanged along the vertical direction. Such a result is different from the experimental result.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there are vortexes on both sides of the gas jet flow, and these vortexes are near the free surface. Some researchers [ 37 , 38 ] used the Euler–Euler approach to describe the fluid flow in the gas-stirred ladle and indicated that the width of the plume remained almost unchanged along the vertical direction. Such a result is different from the experimental result.…”
Section: Resultsmentioning
confidence: 99%
“…It mainly solves the mass and momentum conservation equations for each phase independently to analyze the macroscopic characteristics such as motion and distribution of each phase. [23][24][25][26] Euler-Euler is more suitable for engineering description of gas-liquid flow, because it has better tolerance to the grids number and time step, and better compatibility to coupled heat transfer, mass transfer and phase reaction [27][28][29][30][31][32][33] . Some researchers also use the Eulerian model to describe the inclusion removal [34][35][36][37][38][39] or desulfurization reaction [40][41][42][43][44] in the gas-stirred ladle.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers also use the Eulerian model to describe the inclusion removal [34][35][36][37][38][39] or desulfurization reaction [40][41][42][43][44] in the gas-stirred ladle. However, it should be noted that the change of bubble size is not considered in these Euler-Euler models, and the bubble size is regarded as a constant, that is, the phenomenon of bubble breakup and coalescence is not considered [27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…They can also decrease the steel product quality. Owing to the important influence of ladle teeming on both the steel cleanness and temperature, it received a great deal of research efforts,1–20 which is illustrated in Table 1.…”
Section: Introductionmentioning
confidence: 99%